Iot Based Water Quality Testing System In Aquaculture (International journal of engineering and advanced technology, 2019)
An Aquaculture delivers more protein to address worldwide yearning, bolster the economy, make more occupations and furthermore uses our assets all the more productively, amplifying the utilization of our territory and water. About portion of the world's fish is an aftereffect of aquaculture. The water quality in aquaculture is checked utilizing sensors to guarantee development and survival of oceanic life. The detected information is exchanged to web utilizing Raspberry pi module. The framework naturally evacuates the waste water and fills the crisp water utilizing engine siphon.